2012
DOI: 10.1186/ar3753
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of AAV2-CTLA4IgG decreases sialadenitis and improves gland function in the C57BL/6.NOD-Aec1Aec2 mouse model of Sjögren's syndrome

Abstract: IntroductionCytotoxic T-lymphocyte antigen 4 (CTLA-4) is a key negative costimulatory molecule that displays a wide range of anti-inflammatory properties and is currently approved to treat rheumatoid arthritis as a recombinant fusion protein (CTLA4IgG). To better understand the role of CTLA4IgG in primary Sjögren's syndrome (pSS), we generated a recombinant adeno-associated virus vector serotype 2 (AAV2) expressing a chimera of mouse CTLA-4 fused with a human immunoglobulin (AAV2-CTLA4IgG) and observed the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…Research has shown SjS patients’ salivary gland epithelial cells express antigen-presenting molecules MHC class I and II, as well as, express CD86 and ICAM-1 co-stimulatory molecules [3, 33-36]. Of note,localized delivery of CTLA-4-Ig recombinant fusion protein tothe salivary gland epithelial cellsof B6DC mice prevented disease progression [41],indicating that costimulation from salivary gland epithelial cells arequirement for SjS progression. Expression of CD86 is well documented to be highly expressed in salivary gland epithelial cells of SjS patients [33, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown SjS patients’ salivary gland epithelial cells express antigen-presenting molecules MHC class I and II, as well as, express CD86 and ICAM-1 co-stimulatory molecules [3, 33-36]. Of note,localized delivery of CTLA-4-Ig recombinant fusion protein tothe salivary gland epithelial cellsof B6DC mice prevented disease progression [41],indicating that costimulation from salivary gland epithelial cells arequirement for SjS progression. Expression of CD86 is well documented to be highly expressed in salivary gland epithelial cells of SjS patients [33, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in CD80 in the salivary gland epithelial cells could impact both the ability to activate Tregs and to inhibit effector T-cells directly. Importantly, full functionality of Tregs are shown to be biased towards CD80-CTLA-4 and CD80-PD-L1 interactions [26, 27, 31, 43], while CD86-CD28 interactions are prone to be inhibitory in Tregs [24, 25, 28, 29] and may contribute to SjS progression [35, 36, 41, 44]. Therefore, in vitro and in vivo testing to identify specific functional consequences of miR-146a and the imbalance of CD86:CD80 in the salivary epithelial cells on T-cell responses are currently in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, impedance of cytotoxic T-lymphocyte antigen 4 (CTLA-4), which is a key negative co-stimulatory molecule that displays a wide range of anti-inflammatory properties, seems to offer beneficial effects [40]. The recombinant fusion protein CTLA4IgG, which consists of the extracellular portion of murine CTLA-4 and the Fc portion of human IgG1, is currently approved to treat rheumatoid arthritis and is now in clinical trials for the treatment of SS.…”
Section: Glandular Disordersmentioning
confidence: 99%
“…Theoretically, transferring the CTLA4IgG cDNA offers the possibility of local expression of this immunomodulatory protein in the salivary glands to gain continuous benefit. That hypothesis has been evaluated in mouse models and its efficacy in blocking B7 expression on macrophages in vitro also has been assessed [40]. In this study CTLA4IgG expressed locally in the salivary glands of C57BL/6.NOD-Aec1Aec2 mice (another, more specific model of SS) inhibited of the loss of salivary gland activity and decreased T and B cell infiltration, as well as dendritic cells and macrophages, in the glands, compared with findings in control mice.…”
Section: Glandular Disordersmentioning
confidence: 99%
“…Studies in the C57BL/6.NOD- Aec1Aec2 mouse model of SS have demonstrated benefits of gene therapy with adeno-associated virus (AAV2) in delivering immunomodulatory proteins either locally or systemically. Administration of CTLA4IgG via retrograde instillation of AAV2-CTLA4IgG into salivary glands led to decreased sialadenitis and increased salivary gland function [13]. Low levels of CTLA4IgG were detected in serum and a trend toward improved lacrimal gland function was noted.…”
Section: Treatmentmentioning
confidence: 99%